Compatibility of distributive leadership, teacher autonomy and school effectiveness in Nigeria - Bashir, Karima; Alam, Gazi Mahabubul (Inderscience Publishers, 2024)
Distributive leadership has been linked with teacher autonomy, school effectiveness and decentralisation. This study aims to explore the compatibility of distributive leadership with teacher autonomy and school effectiveness in northwest Nigeria. The paper employs a quantitative method, using a descriptive survey and adopting western designed instruments to make its argument. The selected sample includes 314 federal secondary school principals. The findings revealed that teachers vary in their perception regarding the application of distributive leadership and their autonomy and distributive leadership has a positive direct effect on school effectiveness (β = 0.645, P<0.001), while teacher autonomy has no direct effect on school effectiveness (β = 0.031, P = 0.678). These findings highlight that distributive leadership alone does not rectify school ineffectiveness. This paper responds to the call for more literature from a non-western perspective, providing insights on the paradox of distributive leadership, teacher autonomy and school effectiveness in a decentralised context in Nigeria.